Identification and selection of reference genes for gene expression analysis by quantitative real-time PCR in Suaeda glauca’s response to salinity - Meng Wang; Tingting Ren; Prince Marowa; Haina Du; Zongchang Xu (Scientific Reports, 2021)
Abstract Quantitative real-time polymerase chain reaction (qPCR) using a stable reference gene is widely used for gene expression research. Suaeda glauca L. is a succulent halophyte and medicinal plant that is extensively used for phytoremediation and extraction of medicinal compounds. It thrives under high-salt conditions, which promote the accumulation of high-value secondary metabolites. However, a suitable reference gene has not been identified for gene expression standardization in S. glauca under saline conditions. Here, 10 candidate reference genes, ACT7, ACT11, CCD1, TUA5, UPL1, PP2A, DREB1D, V-H + -ATPase, MPK6, and PHT4;5, were selected from S. glauca transcriptome data. Five statistical algorithms (ΔCq, geNorm, NormFinder, BestKeeper, and RefFinder) were applied to determine the expression stabilities of these genes in 72 samples at different salt concentrations in different tissues. PP2A and TUA5 were the most stable reference genes in different tissues and salt treatments, whereas DREB1D was the least stable. The two reference genes were sufficient to normalize gene expression across all sample sets. The suitability of identified reference genes was validated with MYB and AP2 in germinating seeds of S. glauca exposed to different NaCl concentrations. Our study provides a foundational framework for standardizing qPCR analyses, enabling accurate gene expression profiling in S. glauca.